Dinamika Perubahan Kurikulum di Indonesia dalam Perspektif Kebijakan Pendidikan Nasional dan Pendidikan Islam - Maryani; Pera Trimurniyati; Abhanda Amra (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the dynamics of curriculum change in Indonesia from the perspective of national education policy and Islamic education. The study uses a qualitative approach with a literature review. Data sources come from journal articles, scientific books, education policy documents, and Islamic education literature published in the 2014–2024 period. Data were collected through documentation studies and analyzed using content analysis techniques. The results show that curriculum change in Indonesia has shifted from a centralized approach to a more flexible, competency-based, and learner-centered approach, as reflected in the implementation of the Independent Curriculum. These changes are influenced by developments in education policy, technological advances, globalization, and the need for 21st-century competencies. From an Islamic education perspective, curriculum change demonstrates an effort to integrate Islamic values ​​with modern educational innovations through the principle of maintaining good traditions and adopting more relevant updates. The research findings confirm that successful curriculum implementation requires ongoing policy support, educator readiness, and the strengthening of academic, character, and spiritual values ​​in the educational process